Two melts phase separation in the liquid Sb-Sb2S3 system: critical sound wave propagation and metal-non-metal transition - Kakimuma F.; Kojima Y.; Hisakabe M.; Endoh H.; Tsuchiya Y. (EPJ Web of Conferences, 2011)
The sound velocity and magnetic susceptibility as a function of temperature and composition were measured to investigate critical sound wave propagation and metal-non-metal transition in the liquid Sb-Sb2S3 system. The sound velocity in a homogeneous alloy around 60 at.% of Sb decreases very rapidly and the rate of decrease increases as the two melts phase is approached, which is the typical temperature dependence of the sound velocity in a liquid with a miscibility gap. Below the critical point, the sound velocity was measured along the phase boundary. Using those data, the phase boundary was precisely determined. The critical point is located at 901±2°C and 41.5 ±0.5 at.% S, and the critical exponent of the phase boundary is about 1/3. On the other hand, the magnetic susceptibility as a function of temperature and composition indicates that the electronic state is metallic in liquid Sb and non-metallic in molten Sb2Se3, and crossover form the metallic to non-metallic state occurs around the critical composition.